Exploring the Determinants of Becoming a Mentor in Turkish Organizations. (March 2019) - Ozgen, Muhsine Itir; Thatchenkery, Tojo; Rowell, James William
The success of organizational mentoring programs is dependent on employees becoming mentors themselves. This research explores the determinants of individuals' willingness to mentor. It was conducted in 2016, with 175 respondents from six subsidiaries of two Turkish conglomerates. The quantitative study aimed to analyze the relationship between—personal dispositions (Self-Efficacy and Appreciative Intelligence®), organization's situational factors, previous mentoring experiences, expected costs and benefits from mentoring—and willingness to mentor. The results indicated that individuals scoring highly on dispositional variables and expected benefits from mentoring showed a higher propensity to mentor. While practitioners may identify candidates with higher scores on Appreciative Intelligence®, and Expected Benefits Scales, they also need to enable the expected benefıts to be achieved in the organization. This study contributes to the academic literature on understanding mentoring intentions and provides practitioners with actionable recommendations for the recruitment of mentors who in turn may contribute to positive organization change.